S136 Potential therapeutic benefits of the human amniotic epithelium cell secretome during ex-vivo perfusion of donor lungs. (15th November 2016) - Mayes, JW; Jiwa, K; Leaw, B; Tan, J; Lau, S; Borthwick, L; Andreasson, A; Dark, J; Jenkin, G; Lim, R; Fisher, AJ
Abstract : Introduction: Ex-vivo lung perfusion (EVLP) is used to assess and potentially recondition donor lungs that are not initially suitable for transplantation. In a recent UK study, EVLP was associated with higher primary graft dysfunction (PGD) rates compared to standard lung evaluation procedure. PGD is a process characterised by leucocyte-endothelial adhesion and acute lung injury. In this study, donor lung leucocyte content and endothelial activation before and after EVLP was assessed and then the potential of the human amnion epithelial cell (hAEC) secretome to reduce endothelial cell – leucocyte interaction was evaluated. Methods: Donor lung tissue, pre and post EVLP (n = 16), was stained with CD45, neutrophil elastase and IL-1 receptor type I antibodies to assess endothelial activation, and leukocyte recruitment. Human umbilical vein endothelial cells (HUVECs) and human amnion epithelial cells were isolated from term (n = 5) and preterm (n = 5) placentas. HUVECs activated with IL-1β were used for leucocyte rolling and adhesion studies in an in-vitro model. The effects of hAEC-conditioned media (hAEC secretome) on leucocyte rolling, adhesion and HUVEC expression of adhesion molecules (E-selectin, ICAM-1, and VCAM) was assessed. Results: CD45 positive cells in the donor lung vasculature significantly decreased during EVLP ( p = 0.028). Neutrophil elastase positive cells were significantly lower in accepted donor lungs (n = 4) compared to declined lungs (n = 4) ( p = 0.0044). However, IL-1 Receptor Type 1 expression significantly increased after EVLP ( p = 0.048). The hAEC secretome derived from both term and pre-term placentas significantly reduced endothelial ICAM-1 levels, p = 0.013 and p = 0.0085 respectively. This was accompanied by a significant decrease in leucocyte rolling and leucocyte-endothelial adhesion, with both term ( p = 0.041) and preterm ( p = 0.014) hAEC secretome. Discussion: EVLP reduces the intravascular leucocyte content of the donor lung, probably due to the presence of a leucocyte filter in the perfusion circuit. However, the endothelium remains primed to activation with IL-1 receptor expression increasing during EVLP. The secreted products of hAECs reduce endothelial activation and limit leukocyte-endothelial interactions. Further studies are required in a suitable in-vivo model to determine if hAECs, or their secretome, are a potential therapeutic option during EVLP to protect against primary graft dysfunction after reperfusion of the transplanted lung.